USING ARTIFICIAL INTELLIGENCE IN SCREENWRITING: OPPORTUNITIES, CHALLENGES AND PROSPECTS - Артеменко, Марина (SWorldJournal, 2025)
The article examines the role of artificial intelligence in modern screenwriting. It analyzes its capabilities in modeling situations, improving plot logic, finding references and adapting stories for the international market. The study also explores AI’s